A Pd-catalyzed optional approach for the synthesis of dibenzothiophenes. Issue 12 (6th March 2018) - Song, Juan; Wu, Hao; Sun, Wei; Wang, Songjiang; Sun, Haisen; Xiao, Kang; Qian, Yan; Liu, Chao
Abstract : A direct and practical approach for the construction of DBTs was developed via a Pd-catalyzed tandem reaction, in which commercially available o -bromo-iodobenzenes combined with benzene thiols or iodobenzenes combined with o -bromo-benzene thiols were applied. Abstract : A direct and practical approach for the construction of DBTs was developed via a Pd-catalyzed tandem reaction, in which commercially available o -bromo-iodobenzenes combined with benzene thiols or iodobenzenes combined with o -bromo-benzene thiols were applied. These two approaches will provide an alternative for the synthesis of DBT derivatives.